2021
DOI: 10.1097/md.0000000000026928
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the utility of transabdominal ultrasound for evaluation of gastric cancer

Abstract: Background:Clinical discovery/staging of gastric cancer (GC) is crucial in designing the treatment strategies and largely decides GC patients’ survival. Endoscopic ultrasonography (EUS) and computed tomography (CT) are 2 useful GC diagnosis tools. High doses of radiation associated with CT make its use limited, while the process of EUS is stressful, time-consuming, and challenging. Transabdominal ultrasound (TAUS) is a promising candidate to address these shortcomings. This study aimed to meta-analyze the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…[Table /Fig A systematic review and meta-analysis conducted by Zhang Y et al, involving seven papers found that the accuracy of TAUS in detecting Gastric Cancer (GC) is higher for larger tumours and tumours located in the antrum and body of the stomach [19]. This is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…[Table /Fig A systematic review and meta-analysis conducted by Zhang Y et al, involving seven papers found that the accuracy of TAUS in detecting Gastric Cancer (GC) is higher for larger tumours and tumours located in the antrum and body of the stomach [19]. This is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Ultrasonography has relatively few contraindications. However, some studies have also shown that ultrasonography is more accurate and sensitive in advanced gastric cancer, with accuracies and sensitivities of 79.7% and 98.6% in the advanced group and only 38.7% and 61.2% in the early group 40 . Besides, its detection is also affected by body size, abdominal contents, tumor size, and the operator's technique 41 , 42 .…”
Section: Imaging Screening For Egcmentioning
confidence: 99%
“…The gastric wall can be assessed in detail, providing accurate information on the location, number, and depth of the tumors. A recent meta-analysis (Zhang DN et al, 2021) showed an accuracy of gastric filling ultrasonography for gastric cancer of up to 94% [61]. The role of this method in assessing the intraparietal depth of gastric cancers has been reported in the literature; however, the results are inhomogeneous, and studies on large groups of patients are lacking [62].…”
Section: Abdominal Ultrasound (Au)mentioning
confidence: 99%